Banco de imagens digitais e invisibilidade: a falta de representatividade e as questões raciais ocultadas pelos racismo algorítmico. - Almeida, Ana Paula (2024)
This work seeks to establish a research agenda on a specific issue that permeates the media market, which is the lack of racial diversity in digital image banks. With the advent of social networks at the beginning of the 20th century, the use of images to promote the brands and products of companies and entrepreneurs from various sectors of the economy gained even more space and relevance than they had already achieved. However, the images of black people presented in these image banks often reflect racist biases that are expressed in their algorithms, created (most of the time) by white people with no racial or class consciousness. This research aims to map, through a survey of works and cases related to image banks and debate the impact of algorithmic racism on the stereotypical representations of black people in these image banks and its impact on the marketing sector. Thus, we intend to contribute to a critical analysis of the lack of representation of black people in digital image banks and that entrepreneurs in the Creative Industry can reflect on the diversity of the real world in their businesses - thus allowing greater image representation in the ecosystems of social media.